2008
DOI: 10.1073/pnas.0810106105
|View full text |Cite
|
Sign up to set email alerts
|

Embryo fossilization is a biological process mediated by microbial biofilms

Abstract: Fossilized embryos with extraordinary cellular preservation appear in the Late Neoproterozoic and Cambrian, coincident with the appearance of animal body fossils. It has been hypothesized that microbial processes are responsible for preservation and mineralization of organic tissues. However, the actions of microbes in preservation of embryos have not been demonstrated experimentally. Here, we show that bacterial biofilms assemble rapidly in dead marine embryos and form remarkable pseudomorphs in which the bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(129 citation statements)
references
References 32 publications
5
116
1
1
Order By: Relevance
“…Its shape, symmetry, and relations to the nerve foramina strongly suggest that it is an exceptionally preserved trace of the actual brain rather than a fortuitous artifact. This peculiar case of mineralization may be explained by the fact that the brain underwent microbially induced phosphatization shortly before decay (16,17). This could have been favored by locally anoxic conditions inside the braincase and an environment probably saturated with calcium phosphate (hence the concretions).…”
Section: Resultsmentioning
confidence: 99%
“…Its shape, symmetry, and relations to the nerve foramina strongly suggest that it is an exceptionally preserved trace of the actual brain rather than a fortuitous artifact. This peculiar case of mineralization may be explained by the fact that the brain underwent microbially induced phosphatization shortly before decay (16,17). This could have been favored by locally anoxic conditions inside the braincase and an environment probably saturated with calcium phosphate (hence the concretions).…”
Section: Resultsmentioning
confidence: 99%
“…Experiments have shown that animal embryos have a relatively high preservation potential, particularly when enclosed in a fertilization envelope, whereas primary larvae have an extremely low likelihood of being preserved (Raff et al 2006;Gostling et al 2008Gostling et al , 2009). In addition, these experiments have identified the likely mechanism for Doushantuo-type preservation: 3D replication of cells by robust bacterial pseudomorphs followed by phosphate mineralization (Raff et al 2008). The diagenetic and subsequent geological processes that the fossil is subjected to can introduce artefacts (e.g.…”
Section: Box 1: Preservation Of Weng'an Fossilsmentioning
confidence: 98%
“…This 'exceptional preservation' has been observed for decades, but is not addressed by models of fossilization processes wherein an organism is buried and degraded, and spaces left by degrading organics are subsequently filled by precipitation of exogenous minerals. Modes of preservation to explain the persistence of these secondarily mineralized, but originally soft tissues include microbially mediated stabilization [6,7], early diagenetic mineralization or authigenic replacement [8][9][10], 'sulfurization' [11,12] and others (reviewed in [6,13,14]), but few of these preservation modes have been experimentally tested.…”
Section: Introductionmentioning
confidence: 99%